Penambahan Ekstrak Daun Gambir pada Pembuatan Permen Jelly Antioksidan - Anggraini, Meylin Saputri; Santoso, Budi; Yanuriati, Anny (Seminar Nasional Lahan Suboptimal, 2023)
Anggraini, S.M., Santoso, B., dan Yanuriati, A.  2023. Adding gambir leaves extract to the making of antioxidant jelly candy In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 345-357). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).This study aimed to determine the effect of gambier leaf extract addition on the physical, chemical, and functional and sensory characteristics of antioxidant jelly candy. This study used a factorial completely randomized design (CRD) with two treatment factors and each treatment was repeated three times. Factor A was gambier leaf position (young gambier leaves, old gambier leaves, and mixed gambier leaves) and factor B was gambier leaf extract concentration (17.5%, 35%, and 52.5%). Data were processed using analysis of variance (ANOVA), treatments that had a significant effect were further tested using the Honest Differential Test (BNJ) %. The results showed that treatment A (gambir leaf position) had a significant effect on the antioxidant activity of jelly candy, while treatment B (gambir leaf extract concentration) had a significant effect on total phenol and antioxidant activity of jelly candy. The best treatment was A1B3 (mixed gambier leaves; 52.5% gambier leaf extract) with a total phenol value of 142.02 mgGAE/g, ash content 0.55%, pH 5.64, moisture content 17.62%, antioxidant activity 58.10 ppm.